Economic and financial risks of commercial tilapia cage culture in a neotropical reservoir - Brande, Maicon da Rocha; Santos, David Ferreira Lopes; Fialho, Naor Silveira; Proenca, Danilo Cintra; Gallardo Ojeda, Pablo Rodrigo; Godoi, Flavia C. M.; Roubach, Rodrigo; Bueno, Guilherme Wolff (My University, 2023)
The aim of this study was to analyze the financial and economic risks of tilapia cage culture across different production water volumes (m3). The production water volumes evaluated were 10 to 50 thousand m3 (Small Volume, SV), 51 to 150 thousand m3 (Medium Volume, MV), 151 to 300 thousand m3 (Large Volume, LV), and >301 thousand m3 (Extra-Large Volume, ELV). Produc-tivity and economic data were obtained from a commercial Nile tilapia cage farm with 232 net cages installed in a neotropical reservoir, in Brazil, from 2017 to 2019. Cost and profitability analyses, economic feasibility, and risk and sensitivity analyses were performed using a Monte Carlo simulation. The implementation of commercial tilapia cage farming relies mainly on feed prices. The initial investment demand is proportional to the size of the farms. On the other hand, MV, LV, and ELV tilapia farms showed the lowest financial risks despite the higher investments. These farms presented a medium-low risk at&AP;39% probability, whereas the SV farm presented a medium to medium-high risk at 51.17% probability. Thus, fish farms with a production volume above 51 thousand m3 tend to be more profitable and have a&AP;36% probability of low financial and economic risk with a Payback period of fewer than 10 years, mainly due to the lower feed costs per mass of fish produced. This study assists investors in choosing a better path toward a more viable and profitable activity.
Keywords: precision aquaculture; sensitivity analysis; economy; economic feasibility; monte carlo simulation